Corporate governance and firm value: evidence from the Korean financial crisis - Baek, Jae-Seung; Kang, Jun-Koo; Suh Park, Kyung (Journal of Financial Economics, 2004)
During the 1997 Korean financial crisis, firms with higher ownership concentration by unaffiliated foreign investors experienced a smaller reduction in their share value. Firms that had higher disclosure quality and alternative sources of external financing also suffered less. In contrast, chaebol firms with concentrated ownership by controlling family shareholders experienced a larger drop in the value of their equity. Firms in which the controlling shareholders’ voting rights exceeded cash flow rights and those who borrowed more from the main banks also had lower returns. Our results suggest that change in firm value during a crisis is a function of firm-level differences in corporate governance measures.